تحسين التخزين المؤقت في شبكات المعلومات المركزية (خوارزمية احتمالية محسنة) - أحمد أحمد صقر; العاتكي طلال; عاقل أحمد (Latakia University Journal -Engineering Sciences Series, 2019)
ICN (Information Central Networks) is an appropriate alternative to the current Internet, focusing on distributing and retrieving content rather than transferring data between devices over the network. ICN networks follow a specific approach in which caches are used instead of transferring information across network paths from source to consumers. The main objective of the article is to implement a probability storage algorithm that takes into account two criteria (content popularity - distance ratio between nodes and source) to achieve the following objectives: 1. Increase the speed of storage. 2. Reduce the cache replacement rate responsible for serving users. 3. Reduced delivery times. In this article we present a preliminary comparison by simulators to create the proposed probability caching algorithm and demonstrate the gains made by this algorithm. تشكل شبكات المعلومات المركزية ICN (Information Central Networks) بديل مناسب لشبكة الانترنت الحالية حيث تركز على توزيع واستعادة المحتوى بدلاً من نقل البيانات بين الأجهزة عبر الشبكة. تتبع شبكات ال ICN نهج معين تستخدم من خلاله الذواكر المخبئية (Cache) بدلاً من نقل المعلومات عبر المسارات الشبكية من المصدر الى المستخدمين. الهدف الرئيسي من البحث هو تطبيق خوارزمية تخزين احتمالية تأخذ بعين الاعتبار معيارين اثنين (شعبية المحتوى – نسبة المسافة بين العقد والمصدر) لتحقيق الاهداف التالية: 1- زيادة سرعة التخزين المؤقت. 2- تخفيض معدل استبدال ال Cache المسؤولة عن تخديم المستخدمين. 3- تخفيض عدد مرات تسليم المحتوى. نقدم في هذه البحث مقارنة أولية من خلال المحاكات لعمل خوارزمية التخزين المؤقت الاحتمالية المقترحة وإظهار الفوائد التي تقدمها هذه الخوارزمية.